ANALISIS PENERAPAN PENGGUNAAN MEDIA AJAR DI MI TAHFID DARUL MUBIN PRABUMULIH - Yanalia, Fitri; Muhamad Afandi; Husni, Miftahul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education plays an important role in improving the quality of human resources; therefore, teachers are required to manage the learning process effectively and creatively. One effort that can be carried out is through the use of instructional media in classroom activities. The appropriate use of instructional media can help teachers deliver learning materials more clearly and improve students’ interest and understanding. However, in practice, the use of instructional media in schools still faces several challenges, particularly related to limited facilities, teachers’ competencies, and supporting infrastructure. This study aims to analyze the implementation of instructional media use, the obstacles faced by teachers, and the potential for developing instructional media at MI Tahfidz Darul Mubin Prabumulih. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, supported by source and method triangulation. The results show that the use of instructional media at MI Tahfidz Darul Mubin Prabumulih has been implemented in the learning process but has not been carried out optimally. This is due to limited learning facilities and infrastructure, limited teacher competence in utilizing technology-based media, and limited time and budget of the madrasah. Nevertheless, there are potentials that can be developed, such as teachers’ creativity in utilizing simple learning media, teachers’ ability in planning learning activities, and support from the madrasah in improving the quality of learning.